Europe - Averbuck, Alexis; Bain, Carolyn; Baker, Mark; Christiana, Kerry; Di Duca, Marc; Dragicevich, Peter; Elliott, Mark; Fallon, Steve; Filou, Emilie; Garwood, Duncan; Ham, Anthony; Le Nevez, Catherine; et al. (Lonely Planet., 2015)
Lonely Planet Europe is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Tour French chateaux, take boat trips to Greek beaches, hike past Bulgarian monasteries and glug Spanish wine; all with your trusted travel companion. Get to the heart of Europe and begin your journey now!